Controlling venetian blinds based on parametric design; via implementing Grasshopper’s plugins: a case study of an office building in Cairo - Eltaweel, Ahmad; Su, Yuehong (Elsevier, 2017)
Venetian blinds are common type of shading devices and are increasingly operated automatically to overcome the limitations of using manual operation. Automated blinds need to be controlled to maximize benefits of daylight on the aspects of redirecting sunlight, occupant comfort and energy consumption. However, the common control methods are focused on minimizing negative impacts of daylight, but they might fail to maximize the positive impacts of daylight. They may often inaccurately predict a blind’s position, resulting in the undesirable blockage of useful daylight needed.